Implementation of Special Correctional Telecommunication Services in Safeguarding Inmates’ Communication Rights - Endang Ismindari (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The fulfillment of inmates’ communication rights is a fundamental aspect of human rights protection within Indonesia’s correctional system under Law No. 22 of 2022 on Corrections. This study examines the legal basis and implementation of the Special Correctional Telecommunications Service (Warung Telekomunikasi Khusus Pemasyarakatan or Wartelsus) at the Class I Surabaya Correctional Institution. Using an empirical legal research design with a socio-legal approach, data were collected through observations, semi-structured interviews, document analysis, and a review of relevant legal literature. The findings indicate that Wartelsus has been implemented in accordance with statutory regulations through standardized procedures, effective supervision, and equitable access policies, including complimentary communication vouchers for economically disadvantaged inmates. The study concludes that Wartelsus effectively safeguards inmates’ communication rights while supporting rehabilitation, social reintegration, institutional security, and the broader protection of human rights within Indonesia’s correctional system.